The design of a new bacon product : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Food Technology at Massey University - Wilkinson, Brian Herbert Patrick (Massey University, 1975)
An initial examination of the New Zealand domestic meat market showed that the bacon industry was most in need of help from the development of new products. Per capita consumption of bacon and ham, products which provided almost 70% of the bacon industry's revenue, were shown to be declining. The aim of the project was to design new cured meat products which would replace bacon as the major revenue centre for the industry. A market survey and two consumer surveys were carried out in Palmerston North with the aim of determining the reasons for the apparent decline in bacon and ham consumption. The three surveys were extended to include beef, sheep meat and pork cuts as well as ham, bacon and smallgoods so that the most consumer-acceptable cuts could be identified.The market survey showed that the industry was in fact selling their bacon and ham through the most important retail outlets and while poor advertising and packaging might have been partly responsible for the decline in per capita consumption of bacon and ham, they did not appear to be the major cause. The first consumer survey was carried out to see whether any changes in socio-economic factors such as household size, gross income of the household head or age of the housewife were responsible for the decline in consumption of bacon and ham. Trends evidenced in the New Zealand society since 1966, rather than contributing to the apparent decline in consumption of these products, were in actual fact favouring the consumption of these two meats. The second consumer survey evaluated the attitudes of thirty Palmerston North housewives towards bacon and ham as well as a number of other meats. This survey identified the reasons for the apparent decline in consumption of bacon and ham. Bacon, in particular, was seen to have intermediate properties, intermediate between fresh meat and smallgoods. The data from this second survey was examined by way of Principal component factor analysis and the following variables were isolated as being common to all meats: preference, nutrition, flavour, prestige and length of cooking. An analysis of main meal and snack meats identified additional variables which were unique to each meat group and still other variables were isolated for individual meat cuts. Together, these were hypothesised to be the blueprints for the individual products which enabled consumers to identify each meat product from a whole host of other meat products. The consumer-acceptable meats were examined and the attributes responsible for the success of these products were identified and new cured products were designed, and these attributes were built into them.
Keywords: New Zealand Bacon industry; Bacon